Systemic Crisis, Systemic Fear: An Exchange - Andrew Kliman; Shimshon Bichler; Jonathan Nitzan (Journal of Critical Globalization Studies, 2011)
An exchange between Andrew Kliman and Shimshon Bichler and Jonathan Nitzan. 1. Andrew Kliman: 'Value and Crisis: Bichler and Nitzan versus Marx' EDITORS' NOTE: In the first article, Andrew Kliman responds to Bichler and Nitzan's recent paper on 'Systemic Fear, Modern Finance and the Future of Capitalism' (2010). He then goes on to raise a series of issues concerning the critique of Marxian value theory which these authors put forward in their book Capital as Power (Nitzan and Bichler, 2009). It is followed by a rejoinder from Bichler and Nitzan. 2. Shimshon Bichler and Jonathan Nitzan: 'Kliman on Systemic Fear: A Rejoinder' EDITORS' NOTE: Andrew Kliman's paper in this issue, 'Value and Crisis: Bichler and Nitzan versus Marx', consists of two sections. The first section deals with Bichler and Nitzan's recent paper on 'Systemic Fear, Modern Finance and the Future of Capitalism' (2010). The second section takes issue with their earlier critique of Marx's labour theory of value (Nitzan and Bichler, 2009), and offers an explanation of the global economic crisis. In the following rejoinder, Bichler and Nitzan address the points raised in the first of these sections.
Keywords: 330; behavioural finance; capital; capitalization; distribution; dogma; fear; labour theory of value; major bear markets; Marxism; power; profit; science; sleepwalking; systemic crisis